Head and neck small-cell carcinoma: A multicenter study of 39 cases from 10 institutions - Matsuyama, Hiroshi; Ueki, Yushi; Okamoto, Isaku; Nagao, Toshitaka; Honda, Kohei; Yamazaki, Keisuke; Okabe, Ryuichi; Togashi, Takafumi; Shodo, Ryusuke; Ota, Hisayuki; Takahashi, Takeshi; Omata, Jo; et al. (Frontiers in Surgery, 2022)
Objective: Basal information of head and neck small-cell carcinoma (HNSmCC) including epidemiology, primary site, treatment, and prognosis remains sparse due to its rarity. We report here a multicenter retrospective study on the diagnosis, treatment, and outcomes of patients with HNSmCC. Materials and Methods: This study involved 47 patients with HNSmCC from 10 participating institutions. Eight patients were excluded for whom no pathological specimens were available (n=2) and for discrepant central pathological judgements (n=6). The remaining 39 patients were processed for data analysis. Results: As pretreatment examinations, computed tomography (CT) was performed for the brain (n=8), neck (n=39), and chest (n=32), magnetic resonance imaging (MRI) for the brain (n=4) and neck (n=23), positron emission tomography-CT (PET-CT) in 23 patients, bone scintigraphy in 4, neck ultrasonography in 9, and tumor markers in 25. Primary sites were oral cavity (n=1), nasal cavity/paranasal sinuses (n=16), nasopharynx (n=2), oropharynx (n=4), hypopharynx (n=2), larynx (n=6), salivary gland (n=3), thyroid (n=2), and others (n=3). Stages were II/III/IV-A/IV-B/IV-C/Not determined = 3/5/16/6/5/4; stage IV comprised 69%. No patient had brain metastases. First-line treatments were divided into 3 groups: the chemoradiotherapy (CRT) group (n=27), non-CRT group (n=8), and best supportive care group (n=4). The CRT group included concurrent CRT (CCRT) (n=17), chemotherapy (Chemo) followed by radiotherapy (RT) (n=5), and surgery (Surg) followed by CCRT (n=5). The non-CRT group included Surg followed by RT (n=2), Surg followed by Chemo (n=1), RT alone (n=2), and Chemo alone (n=3). The 1-year/2-year overall survival (OS) of all 39 patients was 65.3/53.3%. The 1-year OS of the CRT group (77.6%) was significantly better compared with the non-CRT group (31.3%). There were no significant differences in adverse events between the CCRT group (n=22) and the Chemo without concurrent RT group (n=9). Conclusion: Neck and chest CT, neck MRI, and PET-CT would be necessary and sufficient examinations in the diagnostic set up for HNSmCC. CCRT may be recommended as the first-line treatment. The 1-year/2-year OS was 65.3%/53.3%. This study would provide basal data for a proposing the diagnostic and treatment algorithms for HNSmCC.